2013
DOI: 10.1175/jtech-d-11-00215.1
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Radiance Distributions Measured with Miniaturized Multispectral Radiance Cameras

Abstract: Miniaturized radiance cameras measuring underwater multispectral radiances in all directions at highradiometric accuracy (CE600) are presented. The camera design is described, as well as the main steps of its optical and radiometric characterization and calibration. The results show the excellent optical quality of the specifically designed fish-eye objective. They also show the low noise and excellent linearity of the complementary metal oxide semiconductor (CMOS) detector array that is used. Initial results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Note that there are currently no agreed look-up tables for the Q-factor in turbid coastal waters, but see the simulations made by Loisel and Morel (2001) and Park and Ruddick (2005). The Q-factors measured along river transects during the Malina field campaign, using a miniaturized multispectral (406, 438, 494, 510, 560 and 628 nm) radiance camera (see Antoine et al, 2012 for measurement details), showed very limited spectral variations: maximum variations of 10 % between 406 and 628 nm, 7 % on average, at nadir. While limited to the visible spectral domain, these measurements support the use of a spectrally-flat Q-factor in our model.…”
Section: Ocean Colour Spm Quantification Algorithmmentioning
confidence: 99%
“…Note that there are currently no agreed look-up tables for the Q-factor in turbid coastal waters, but see the simulations made by Loisel and Morel (2001) and Park and Ruddick (2005). The Q-factors measured along river transects during the Malina field campaign, using a miniaturized multispectral (406, 438, 494, 510, 560 and 628 nm) radiance camera (see Antoine et al, 2012 for measurement details), showed very limited spectral variations: maximum variations of 10 % between 406 and 628 nm, 7 % on average, at nadir. While limited to the visible spectral domain, these measurements support the use of a spectrally-flat Q-factor in our model.…”
Section: Ocean Colour Spm Quantification Algorithmmentioning
confidence: 99%
“…Here a novel method is introduced to determine the sea ice and snow anisotropy of a surface ranging from 1 m 2 to 80 m 2 at a hyperangular resolution. The new method relies on a state‐of‐the‐art multispectral circular fish‐eye radiance camera manufactured by CIMEL Electronique (Paris, France) and allows instantaneous radiance measurements over a hemisphere at about 1° and six different visible spectral bands, referred to as the CE600 (Antoine et al, ). In addition, reflectance anisotropy was also measured with a hyperspectral field spectroradiometer manufactured by Analytical Spectral Device, Inc. (hereafter referred to as ASD) mounted on a goniometer.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of water molecular scattering is included in the under-light model (details can be found in Sayer et al, 2010). Recent measurements also report on the angular dependence of the ocean surface reflectance (e.g., Voss and Chapin, 2005;Antoine et al, 2013). However, it is not clear how general these results might be, so including this refinement is beyond the scope of the current study; having additional constraints on ocean surface BRDF would be an asset to multi-angle remote sensing of Earth's surface.…”
Section: Ocean Surface Modelmentioning
confidence: 99%